IDENTIFICATION AND MOLECULAR CHARACTERIZATION OF NATIVE STRAINS OF LACTOBACILLUS ISOLATES FROM POULTRY LITTER - Shiva, Carlos (2013)
The aim of this study was to isolate and identify bacteria of Lactobacillus genus from poultry litter with 1, 2 or 3 uses and low ammonia records. Resistance for conditions at pH 5 and 8 was evaluated as well as the ability to inhibit activity in urease bacteria (Staphylococcus spp and Pseudomona spp) isolated from poultry litter. Seventy three suspected colonies of Lactobacillus were identified by culture in selective media and morphological patterns. Gram staining and catalase test revealed that only 19 strains were of Lactobacillus genus. Furthermore, through PCR was found that 53% corresponded to L. reuteri, 32% to L. plantarum, 10% to L. vaginalis and 5% to L. salivarius. All isolates survived at conditions of pH 5 and 8 and all strains produced some type of active biocin against Staphylococci spp or Pseudomona spp which might be useful as additive to regulate the microbiota in poultry litter.